Communist Party Nominees versus Modernizers: Power Struggle in Odessa and the Odesssa Region in 1990–1998 - Skrukwa, Grzegorz (Sensus Historiae, 2022)
The article presents a conflict in Odessa and the Odessa region that took place in the years 1990–1998 between two groups of elite: the former Communist Party nominees and the so-called modernizers, i.e. people who entered business and politics during the perestroika period. The representative of the first group was Ruslan Bodlan, former First Secretary of the Communist Party in the region, then governor of the region in 1994–1998. The representative of the second group was Eduard Hurvic, Mayor of Odessa in 1994–1998. The underlying cause of the conflict was actually a divergence of economic interests regarding privatization - one side wanted to benefit from the state economy for as long as possible, while the other one pushed for privatization. The conflict reached its apogee in 1998, when President Leonid Kuchma interfered in the process of electing the Odessa mayor, and it contributed to the fact that in Odessa, unlike in Donetsk, Dnipropetrovsk, and Kharkiv, the so-called oligarchic clan has not formed.